A RDF-based approach to metadata crosswalk for semantic interoperability at the data element level. Issue 2 (15th June 2015) - Chen, Ya-Ning
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a Resource Description Framework (RDF)-based approach to transform metadata crosswalking from equivalent lexical element mapping into semantic mapping with various contextual relationships. RDF is used as a crosswalk model to represent the contextual relationships implicitly embedded between described objects and their elements, including semantic, hierarchical, granular, syntactic and multiple object relationships to achieve semantic metadata interoperability at the data element level. Design/methodology/approach – This paper uses RDF to translate metadata elements and their relationships into semantic expressions, and also as a data model to define the syntax for element mapping. The feasibility of the proposed approach for semantic metadata crosswalking is examined based on two use cases – the Archives of Navy Ships Project and the Digital Artifacts Project of National Palace Museum in Taipei – both from the Taiwan e-Learning and Digital Archives Program. Findings – As the model developed is based on RDF-based expressions, unsolved issues related to crosswalking, such as sets of shared terms, and contextual relationships embedded between described objects and their metadata elements could be manifested into a semantic representation. Corresponding element mapping and mapping rules can be specified without ambiguity to achieve semantic metadata interoperability. Research limitations/implications – Five steps were developed to clarify the details of the RDF-based crosswalk. The RDF-based expressions can also serve as a basis from which to develop linked data and Semantic Web applications. More use cases including biodiversity artifacts of natural history museums and literary works of libraries, and conditions, constraints and cardinality of metadata data elements will be required to make revisions to fine tune the proposed RDF-based metadata crosswalk. Originality/value – In addition to reviving contextual relationships embedded between described objects and their metadata elements, nine types of mapping rules were developed to achieve a semantic metadata crosswalk which will facilitate the design of related mapping software. Furthermore, the proposed approach complements existing crosswalking documents provided by authoritative organizations, and enriches mapping language developed by the CIDOC community.